2018
DOI: 10.1108/ejtd-06-2016-0042
|View full text |Cite
|
Sign up to set email alerts
|

The role of community engagement in building sustainable health-care delivery interventions for Kenya

Abstract: Purpose The purpose of this article is to provide a general review of the health-care needs in Kenya which focuses on the role of community engagement in facilitating access and diminishing barriers to quality care services. Health-care concerns throughout Kenya and the culture of Kenyan’s health-care practices care are considered. Design/methodology/approach A comprehensive review covered studies of community engagement from 2000 till present. Studies are collected using Google Scholar, PubMed, EBSCOhost an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The HRD community is steadily producing quality research focused on African experiences. Recent works include studies of learning transfer (Kiwanuka, Miiro, Matsiko, & Nkalubo, 2020;Suleiman, Dassanayake, & Abang Othman, 2018), teacher training (Oonyu, 2019), higher education (Johnson, 2019), skills & capabilities development (Arubayi & Akobo, 2018;Oats & Gumbo, 2019;Otchia & Yamada, 2019;Yamada, Otchia, & Taniguchi, 2018), healthcare and literacy systems (Akello, Lutwama-Rukundo, & Musiimenta, 2017;Davis, Arana, Creel et al, 2018;Davis, Menser, Juarez, Tomaszewski, & Kash, 2019;Regmi, 2019;Wekullo, Davis, Nafukho, & Kash, 2018), promoting learning (Biney, 2019), and leadership development (Modisane, 2018) post-coloniality and NHRD (Ekuma, 2019), and collaborations in North-South scientific international projects (Lutomia, 2019). While various components of program planning are discussed throughout this literature, none of the recent studies center a planning process in their research.…”
Section: Recent Hrd Literature Centering African Perspectivesmentioning
confidence: 99%
“…The HRD community is steadily producing quality research focused on African experiences. Recent works include studies of learning transfer (Kiwanuka, Miiro, Matsiko, & Nkalubo, 2020;Suleiman, Dassanayake, & Abang Othman, 2018), teacher training (Oonyu, 2019), higher education (Johnson, 2019), skills & capabilities development (Arubayi & Akobo, 2018;Oats & Gumbo, 2019;Otchia & Yamada, 2019;Yamada, Otchia, & Taniguchi, 2018), healthcare and literacy systems (Akello, Lutwama-Rukundo, & Musiimenta, 2017;Davis, Arana, Creel et al, 2018;Davis, Menser, Juarez, Tomaszewski, & Kash, 2019;Regmi, 2019;Wekullo, Davis, Nafukho, & Kash, 2018), promoting learning (Biney, 2019), and leadership development (Modisane, 2018) post-coloniality and NHRD (Ekuma, 2019), and collaborations in North-South scientific international projects (Lutomia, 2019). While various components of program planning are discussed throughout this literature, none of the recent studies center a planning process in their research.…”
Section: Recent Hrd Literature Centering African Perspectivesmentioning
confidence: 99%
“…One study did not focus on the age range of 14 to 49 years old [31]. Six studies presented evidence on general healthcare [7,[32][33][34][35][36]. Eight studies reported on sexual and reproductive healthcare services [37][38][39][40][41][42][43][44].…”
Section: Selection Of Sources Of Evidencementioning
confidence: 99%
“…Fiteen studies reported on maternal healthcare services [45][46][47][48][49][50][51][52][53][54][55]. Three studies were literature reviews [3,34,56].…”
Section: Selection Of Sources Of Evidencementioning
confidence: 99%